Lest Formalisms Impede Insight and Success: Evaluation in Health Informatics - Moehr, J. R.; Anglin, C.; Schaafsma, J.; Pantazi, S.; Grimm, N. (Methods of Information in Medicine, 2006)
Objectives: To illustrate the advantages of an open-ended formative evaluation approach using a project-specific selection of methods over the controlled trial approach in the evaluation of health information systems. To illustrate factors leading to success and others impeding it in a telehealth project.Methods: The methods and results of an evaluation of the BC Telehealth Program are summarized.Results: The evaluation gave a comprehensive picture of the project, including assessment of the effects of an array of telehealth applications, and their economic impact. Factors leading to success and others preventing it are identified from the level of overall program management to the project specifics. The results include unanticipated effects and explanations for their reasons of occurrence. Neither the comprehensiveness of information nor the timeliness was achieved in a related project using a controlled trial approach.Conclusions: Not all types of health information system projects can be evaluated using the controlled trial approach. This approach may impede important insights. It is also usually much less efficient. Funding agencies and journal editors have to take this into account when selecting projects for funding and submissions for publication.
Keywords: Telemedicine; medical informatics; evaluation studies; Canada